Effects of temperature, strain-rate & hygrothermal aging on the mechanical properties of composites - Muhammad Johan Jamil. (2013)
Fiber Reinforced Polymer (FRP) composites are fast becoming the material of choice for underwater marine applications due to their high strength to weight ratio and good corrosion resistance. However, FRP composites utilized in marine applications